Advances in Coatings Deposition and Characterization (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Coatings offer the unique opportunity to create architectures that combine the functionality of two or more materials, conferring unique properties to objects with an extremely large palette of solutions. For this flexibility, thick and thin films have terrific impacts on the most relevant societal challenges. Computers, food packaging, airplanes, and cars, to mention a few familiar objects from everyday life, rely heavily on coatings. To celebrate the key role that coatings have in society, and in science and technology, this book collects a selection of relevant reviews and original research articles published in "Coatings" in 2017 and 2018. Papers have been selected based on their broad impact and balancing between the two major aspects of coatings science and technology: deposition and characterization.